Theoretical calculation of the exchange coupling constant in some polymeric nickel(II) complexes using range-separated functionals - Makhyoun, Mohamed Abdalla; Massoud, Raghdaa Adel (European Journal of Chemistry, 2018)
The magnetic parameters (J, g) of two nickel(II) 1D polymers (Ni(en)(ox) and Ni(ox) (ampy)2; where en = ethylene diamine, ox = oxalate, ampy = 4-amino-pyridine) were calculated using 6-311+G* basis set and six range-separated DFT functionals (CAM-B3LYP, LC-BLYP, wB97, wB97X, wB97X-D3 and B2T-PLYP) together with the hybrid B3LYP method for sake of comparison. We found that the wB97, CAM-B3LYP and wB97X-D3 methods gave approximate value of J for compound 1 and the B2T-PLYP method was found to be the best method for compound 2. The g values were calculated by the coupled perturbed approach. However, we assume that a higher approximation is needed in order to give satisfactory results for g. A new equation has been proposed to relate the experimental susceptibility to the J and g parameters. The Curie-Weiss law was included in this equation resulting in a good explanation of the steep part of the experimental curve below 20 K.